Maintaining Intreraction in the EFL Online Classroom - Zusana E. Pudyastuti (IC-ITECHS, 2020)
Nowadays, the internet has influenced teachers and students’ life in every aspects. Embracing the internet in the online learning is unavoidable. Even though traditional classroom is still considered as the best method of delivery, but online learning also brings many benefits for both teachers and students. This paper presents a review of some literature highlighting the interaction in the online EFL classroom. Designing an online EFL classroom needs a careful planning because it is related to the language learning skills and the digital literacy learning skills that the students should comprehend. To make the design successful, all types of interactions sould be maintained the the online EFL classroom. Two types of online learning, which are synchronous and asynchronous learning, must provide the students an opportunity to build their knowledge by working collaboratively and having interaction with the sutdents and teacher to be able to learn better. The interaction is multiple which needs different methods for each conditions or a combination of several methods of interactions. The careful design planning and the appropriate choosen of interaction and collaboration methods provide the students with a safe environment for better engagement and active participation. The teacher presence, consists of social presence, teaching presence and cognitive presence, is very important in the online EFL classroom for maintaining and building the interaction with the students because the students tend to be passive. The teacher presence and the interaction in the online EFL classroom can be accommodated in many online applications used in the language learning.